Polypropylene composition
By using a composition of high and low isotactic regularity polypropylene produced by a single active center catalyst, the problem of degradation of the mechanical properties of polypropylene after sterilization is solved, and the effect of improving the anti-aging and ductility retention of the polypropylene composition is achieved.
Patent Information
- Application Number
- CN202380064951.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-09-09
- Filing Date
- 2023-09-08
- Publication Date
- 2025-04-18
AI Technical Summary
The mechanical properties of polypropylene change over time after processing, especially during the sterilization process, toughness and ductility will be significantly reduced, resulting in material embrittlement problems.
The mechanical properties of the polypropylene compositions produced from single active center catalyst (SSC) are improved by combining these two polypropylene.
The polypropylene composition exhibits good anti-aging properties in terms of ductility retention, and can maintain high ductility and toughness after sterilization, thereby reducing the embrittlement of the material.
Smart Images

Figure BDA0005303988520000051 
Figure BDA0005303988520000091 
Figure BDA0005303988520000101
Abstract
Description
Technical Field
[0001] The present invention relates to a polypropylene composition. More particularly, the present invention relates to a polypropylene composition comprising a combination of two polypropylenes (PP) produced using a single-site catalyst (SSC), in particular a high isotacticity SSC-PP and a low isotacticity SSC-PP. The present invention further relates to an article comprising the polypropylene composition and the use of the low isotacticity SSC-PP of the propylene composition described herein for improving the mechanical properties of the polypropylene composition. Background Art
[0002] Polypropylene (PP) is one of the most commonly used plastics in packaging applications.
[0003] However, it is well known that the mechanical properties of polypropylene change over time after processing, with a gradual increase in stiffness and a decrease in toughness being observed due to a combination of physical aging and post-crystallization. It is known from the effects of steam sterilization or pasteurization that this process can change the toughness and ductility (especially of PP homopolymer) to a critical extent. These changes in mechanical properties can be even more pronounced in the case of polypropylene subjected to radiation-based sterilization processes such as gamma-irradiation, where chemical degradation often also occurs.
[0004] In a growing part of the polypropylene market, especially in the pharmaceutical field, and in food packaging, especially in medical applications (syringes, bags, tubes, etc.), the material is sterilized by heat (steam), radiation (β / electrons or γ) or chemicals (mainly ethylene oxide), which affects the mechanical and optical properties. Among all of these, sterilization via γ-radiation is the most relevant method for sterilizing drugs, medical or diagnostic items. It is well known that radiation (mainly the ionizing effect of γ-rays) causes chain scission and degradation effects, resulting in reduced melt viscosity and severe embrittlement. What makes this free radical reaction so critical is that it lasts for a long time after the actual sterilization process, making long-term studies necessary for studying the effects. Various strategies have been published to counter the effects of sterilization. Some strategies focus on the use of "mobilizing agents" (paraffin oils) and special stabilizer formulations. Other strategies combine polypropylene with specific polyethylene grades or other polymers, such as EP 0847420, JP 4808419 and KR 2005053937.
[0005] However, an area that has received less attention is how to address the effects of sterilization as well as the issues of normal physical aging and post-crystallization. Therefore, modifiers that are effective in minimizing the changes caused by the combination of these two sources are of interest. Ideally, such components should change the original properties of polypropylene as little as possible, should not migrate and be non-toxic.
[0006] The present inventors have sought to develop new polypropylene compositions, in particular for the healthcare and medical markets, which have improved resistance to ageing both with and without exposure to sterilization processes by gamma-irradiation.
[0007] The inventors have surprisingly found that polypropylene compositions comprising two polypropylenes (PP) produced using a single site catalyst (SSC), in particular a high isotacticity SSC-PP and a low isotacticity SSC-PP, provide an attractive solution. In particular, these polypropylene compositions have good aging resistance in terms of ductility retention, which is measured by the relative strain at break after a specific period of time. Notably, this effect is also observed after sterilization. Summary of the invention
[0008] Thus, viewed from a first aspect, the invention provides a polypropylene composition having a melt flow rate (MFR2) when measured according to ISO 1133 at 230°C under a load of 2.16 kg of from 1 to 100 g / 10 min, the composition comprising:
[0009] a) 80 to 96 wt.-%, based on the total weight of the polypropylene composition, of a high isotacticity polypropylene based on a single site catalyst (SSC), the high isotacticity polypropylene having an MFR2 according to ISO 1133 at 230° C. under a load of 2.16 kg of 1 to 100 g / 10 min and a melting temperature (T ) determined by differential scanning calorimetry (DSC) in the range of 148 to 160° C. m ), wherein the high isotacticity polypropylene is
[0010] (i) a polypropylene homopolymer; or
[0011] (ii) propylene and selected from ethylene and C4-C 10 A random propylene copolymer of at least one comonomer of an alpha-olefin, wherein the at least one comonomer is present in an amount of up to 0.5 wt. % relative to the total weight of the copolymer; and
[0012] b) 4 to 20 wt.-%, relative to the total weight of the polypropylene composition, of a low isotacticity polypropylene homopolymer based on a single site catalyst (SSC), the low isotacticity polypropylene homopolymer having a melting temperature (T) determined by differential scanning calorimetry (DSC) in the range of 135 to 147°C. m ) and a xylene cold soluble (XCS) content according to ISO 16152 in the range of 2 to 10 wt.-% relative to the total weight of the low isotactic propylene homopolymer.
[0013] Viewed from another aspect the invention provides an article comprising a polypropylene composition as hereinbefore defined.
[0014] Viewed from a further aspect the invention provides the use of a single site catalyst based low isotacticity polypropylene homopolymer as hereinbefore defined for improving the retention of ductility measured as relative strain at break after 7 days of a polypropylene composition as hereinbefore defined.
[0015] definition
[0016] The term "polypropylene" will be understood to mean a propylene-based polymer, i.e. a propylene-based polymer comprising at least 50 wt% propylene based on the total weight of the entire polymer. The terms "polypropylene" and "propylene polymer" refer to the same object and can be used interchangeably.
[0017] In the context of the present invention, the term "gamma sterilizable" means that the polymer can be sterilized by using gamma-irradiation. Those skilled in the art are familiar with gamma sterilization techniques. Gamma sterilization is typically performed at a dose in the range of 15 to 150 kGy.
[0018] The term "random copolymer" must preferably be understood according to IUPAC (Pure Appl. Chem., Vol. 68, No. 8, pp. 1591-1595, 1996). The random copolymers encompassed by the invention have a comonomer content less than or equal to 0.5% by weight relative to the total weight of the copolymer.
[0019] The term "high isotacticity" is intended herein to mean that the polypropylene has a high level of isotacticity. As is known in the art, isotacticity is a measure of the stereoregularity at the chiral centers in the propylene monomer units. In the context of the present invention, isotacticity is measured by pentad regularity. <mmmm>The term "high isotacticity" refers to a structure having at least 95 mol % of isotacticity. 13 C-NMR spectroscopy <mmmm>Fraction.
[0020] The term "low isotacticity" is intended herein to mean that the polypropylene has a low level of isotacticity. As is known in the art, isotacticity is a measure of the stereoregularity at the chiral centers in the propylene monomer units. In the context of the present invention, isotacticity is measured by pentad regularity. <mmmm>The measure of the fraction is provided, and "low isotacticity" means having a maximum of 90 mol % of 13 C-NMR spectroscopy <mmmm>Fraction. DETAILED DESCRIPTION
[0021] The present invention relates to a polypropylene composition comprising two components: a high isotacticity polypropylene and a low isotacticity polypropylene. It should be understood that the two polypropylenes are different.
[0022] High isotacticity polypropylene
[0023] The high isotacticity polypropylene may be (i) a polypropylene homopolymer; or
[0024] (ii) propylene and selected from ethylene and C4-C 10 A random propylene copolymer of at least one comonomer of an alpha-olefin, wherein the at least one comonomer is present in an amount of up to 0.5 wt.-% relative to the total weight of the copolymer.
[0025] In one embodiment (i), the high isotactic polypropylene is a polypropylene homopolymer. According to the present invention, the expression "polypropylene homopolymer" relates to a polypropylene consisting essentially of propylene units, i.e. a polypropylene consisting of at least 99.5 mol%, more preferably at least 99.6 mol%, still more preferably at least 99.7 mol%, such as at least 99.9 mol% of propylene units. In another embodiment, only propylene units are detectable, i.e. only propylene has been polymerized. The definition "propylene homopolymer" has a well-known meaning in the art.
[0026] In an alternative embodiment (ii), the high isotactic polypropylene is propylene and a polypropylene selected from ethylene and C4-C 10 The invention relates to random propylene copolymers of at least one comonomer of α-olefins. In a preferred embodiment, the at least one comonomer is selected from ethylene and C4 to C8 α-olefins, more preferably selected from ethylene and butene. Most preferably, the at least one comonomer is ethylene. Although within the scope of the present invention, the copolymer contains more than one comonomer, such as a mixture of two or more comonomers, it is preferred that only a single comonomer is present.
[0027] In this embodiment, at least one comonomer is present in an amount of up to 0.5 wt% relative to the total weight of the copolymer. Thus, typical comonomer amounts are in the range of 0.05 to 0.5 wt%, preferably in the range of 0.1 to 0.4 wt%, such as in the range of 0.15 to 0.3 wt%, relative to the total weight of the copolymer. When more than one comonomer is present, it is understood that these amounts relate to the total amount of all comonomers present.
[0028] High isotacticity polypropylene is a single site catalyst (SSC) based polypropylene, which means that it is prepared in the presence of a single site catalyst. The term "single site catalyst" is well known in the art. In addition, those skilled in the art will understand that polymers prepared using single site catalysts will have different properties than polymers prepared using alternative catalysts (such as Ziegler-Natta or chromium catalysts).
[0029] Therefore, high isotactic polypropylene is obtained by polymerization using a single-site catalyst (preferably a metallocene catalyst). The polymerization method used can be any suitable known polymerization method in the art.
[0030] Compared to polypropylene prepared by using Ziegler-Natta (ZN) catalysts, polypropylene prepared by using metallocenes provides a different microstructure. The most significant difference is the presence of regional defects in metallocene-made polypropylene. These regional defects can be of three different types, namely 2,1-erythro (2,1e), 2,1-threo (2,1t) and 3,1 defects. A detailed description of the structure and formation mechanism of regional defects in polypropylene can be found in Chemical Reviews 2000, 100 (4), pages 1316 to 1327.
[0031] Thus, the term "regio defect" is defined herein as the sum of 2,1 erythro regio defects, 2,1 threo regio defects, and 3,1 regio defects. Thus, the amount of defects (i.e., regio defects, such as 2,1 regio defects (i.e., 2,1 erythro regio defects and 2,1 threo regio defects) and 3,1 regio defects) is expressed as "mol %" of the average percentage of propylene units in the polymer chain.
[0032] In a preferred embodiment, the high isotactic polypropylene has a molecular weight of 0.3 to 1.5 mol %, preferably 0.4 to 1.4 mol % and most preferably 0.5 to 1.3 mol %. 13 [2,1]-regio defects determined by C-NMR spectroscopy. The presence of such amounts of regio defects is a sufficient (although not mandatory) feature to unambiguously identify that the polypropylene was produced with a metallocene catalyst rather than a Ziegler-Natta type catalyst.
[0033] The high isotactic polypropylene is characterized by a high isotacticity as defined above. Preferably, the high isotactic polypropylene has 95 to 99.9 mol%, preferably 96.0 to 99.5 mol%, most preferably 96.5 to 99.0 mol% of 13 Pentad regularity determined by C-NMR spectroscopy <mmmm>.
[0034] Metallocene catalysts are defined in particular by formula (I):
[0035]
[0036] In the complex of formula (I), it is preferred that if Mt is Zr or Hf, preferably Zr; each X is a sigma ligand. Most preferably, each X is independently a hydrogen atom, a halogen atom, a C1-C6 alkoxy group or an R' group, wherein R' is a C1-C6 alkyl, phenyl or benzyl group. Most preferably, X is a chlorine, benzyl or methyl group. Preferably, the two X groups are the same. The most preferred options are two chlorides, two methyl or two benzyl groups, especially two chlorides. For further preferred definitions of the residues, reference is made to WO 2019 / 179959.
[0037] Particularly preferred metallocene catalyst complexes are:
[0038] Racemic-trans-dimethylsilylene[2-methyl-4,8-bis-(4'-tert-butylphenyl)-1,5,6,7-tetrahydro-s-indacene-1-yl][2-methyl-4-(3',5'-dimethyl-phenyl)-5-methoxy-6-tert-butylinden-1-yl]zirconium dichloride (MC-1);
[0039] Racemic-trans-dimethylsilylene[2-methyl-4,8-bis-(3',5'-dimethylphenyl)-1,5,6,7-tetrahydro-s-indacene-1-yl][2-methyl-4-(3',5'-dimethylphenyl)-5-methoxy-6-tert-butylindene-1-yl]zirconium dichloride (MC-2);
[0040] Racemic-trans-dimethylsilylene[2-methyl-4,8-bis-(3',5'-dimethylphenyl)-1,5,6,7-tetrahydro-s-indacene-1-yl][2-methyl-4-(3',5'-di-tert-butyl-phenyl)-5-methoxy-6-tert-butylinden-1-yl]zirconium dichloride (MC-3).
[0041] The corresponding dimethyl zirconium analogs of the three catalysts defined above are also possible, but not preferred. The most preferred catalyst is the one used in the examples of the present invention, namely MC-2.
[0042] Catalyst
[0043] In order to form an active catalytic species, it is usually necessary to employ a cocatalyst which is well known in the art. Here, a cocatalyst system comprising a boron-containing cocatalyst and an aluminoxane cocatalyst is usually used in combination with the metallocene catalyst complex defined above.
[0044] Typical aluminoxane cocatalysts are prior art. A preferred aluminoxane is methylaluminoxane (MAO). Since the aluminoxanes used as cocatalysts according to the invention are not pure compounds due to the way they are prepared, the molar concentrations of the aluminoxane solutions hereinafter are based on their aluminum content.
[0045] As mentioned above, the aluminoxane cocatalyst is used in combination with a boron-containing cocatalyst.
[0046] Boron-based cocatalysts of interest include those of formula (Z)
[0047] BY3(Z)
[0048] wherein Y is the same or different and is a hydrogen atom, an alkyl group having 1 to about 20 carbon atoms, an aryl group having 6 to about 15 carbon atoms, an alkaryl group, an aralkyl group, a haloalkyl group, or a haloaryl group, each group having 1 to 10 carbon atoms in the alkyl group and 6 to 20 carbon atoms in the aryl group, or fluorine, chlorine, bromine, or iodine.
[0049] Preferred examples of Y are methyl, propyl, isopropyl, isobutyl or trifluoromethyl, unsaturated groups such as aryl or halogenated aryl groups, such as phenyl, toluyl, benzyl groups, p-fluorophenyl, 3,5-difluorophenyl, pentachlorophenyl, pentafluorophenyl, 3,4,5-trifluorophenyl and 3,5-di(trifluoromethyl)phenyl. Preferred options are trifluoroborane, triphenylborane, tri(4-fluorophenyl)borane, tri(3,5-difluorophenyl)borane, tri(4-fluoromethylphenyl)borane, tri(2,4,6-trifluorophenyl)borane, tri(pentafluorophenyl)borane, tri(tolyl)borane, tri(3,5-dimethyl-phenyl)borane, tri(3,5-difluorophenyl)borane and / or tri(3,4,5-trifluorophenyl)borane. Particularly preferred is tri(pentafluorophenyl)borane.
[0050] Preferred ionic compounds that can be used include triethylammonium tetra(phenyl)borate, tributylammonium tetra(phenyl)borate, trimethylammonium tetra(tolyl)borate, tributylammonium tetra(tolyl)borate, tributylammonium tetra(pentafluorophenyl)borate, tripropylammonium tetra(dimethylphenyl)borate, tributylammonium tetra(trifluoromethylphenyl)borate, tributylammonium tetra(4-fluorophenyl)borate, N,N-dimethylcyclohexylammonium tetra(pentafluorophenyl)borate, N,N-dimethylbenzylammonium tetra(pentafluorophenyl)borate, N,N-dimethylanilinium tetra(phenyl)borate, N,N-diethylanilinium tetra(pentafluorophenyl)borate, N,N-dimethylanilinium tetra(pentafluorophenyl)borate, N,N-di(propyl)ammonium tetrakis(pentafluorophenyl)borate, di(cyclohexyl)ammonium tetrakis(pentafluorophenyl)borate, triphenylphosphonium tetrakis(phenyl)borate, triethylphosphonium tetrakis(phenyl)borate, diphenylphosphonium tetrakis(phenyl)borate, tri(methylphenyl)phosphonium tetrakis(phenyl)borate, tri(dimethylphenyl)phosphonium tetrakis(phenyl)borate, triphenylcarbeniumtetrakis(pentafluorophenyl)borate or ferroceniumtetrakis(pentafluorophenyl)borate.
[0051] Preferred are triphenylcarbonium tetrakis(pentafluorophenyl)borate, N,N-dimethylcyclohexyl ammonium tetrakis(pentafluorophenyl)borate or N,N-dimethylbenzylammonium tetrakis(pentafluorophenyl)borate. Certain boron cocatalysts are particularly preferred. Preferred borates include triphenylcarbonium ions. Therefore, N,N-dimethylammonium tetrakis(pentafluorophenyl)borate and Ph3CB(PhF5)4 and the like are particularly preferred.
[0052] Particularly preferred is the combination of a borate cocatalyst such as triphenylcarbonium tetrakis(pentafluorophenyl)borate and methylaluminoxane (MAO).
[0053] Suitable amounts of promoters are well known to the skilled person.
[0054] The molar ratio of boron to the metal ion of the metallocene may be in the range of 0.5:1 to 10:1 mol / mol, preferably in the range of 1:1 to 10:1, especially in the range of 1:1 to 5:1 mol / mol.
[0055] The molar ratio of Al in the aluminoxane to the metal ion in the metallocene may be in the range of 1:1 to 2000:1 mol / mol, preferably in the range of 10:1 to 1000:1, and more preferably in the range of 50:1 to 500:1 mol / mol.
[0056] The high isotactic polypropylene has a melt flow rate MFR2 (230° C., 2.16 kg) determined according to ISO 1133 in the range of 1 to 100 g / 10 min, preferably in the range of 1.5 to 20 g / 10 min, still more preferably in the range of 2.0 to 15 g / 10 min.
[0057] It is further preferred that the high isotacticity polypropylene is characterized by a rather low xylene cold soluble (XCS) content, i.e. below 2.0 wt.-% xylene cold soluble (XCS) determined according to ISO 16152. Thus, the high isotacticity polypropylene preferably has a xylene cold soluble (XCS) content in the range of 0.1 to 1.9 wt.-%, more preferably in the range of 0.2 to 1.7 wt.-%, yet more preferably in the range of 0.3 to 1.5 wt.-%.
[0058] The amount of xylene cold solubles (XCS) also indicates that the high isotactic polypropylene preferably does not contain any elastomeric polymer components, such as ethylene propylene rubber. In other words, the high isotactic polypropylene is not a heterophasic polypropylene, i.e. a system consisting of a polypropylene matrix in which an elastomeric phase is dispersed. Such a system is characterized by a relatively high xylene cold soluble content. In other words, the high isotactic polypropylene is a single-phase polypropylene. Further, the high isotactic polypropylene is preferably a crystalline propylene polymer. The term "crystalline" means that the high isotactic polypropylene has a relatively high melting temperature. In particular, the high isotactic polypropylene has a melting temperature T measured by differential scanning calorimetry (DSC) according to ISO 11357 in the range of 148 to 160°C, preferably in the range of 150 to 159°C, and more preferably in the range of 152 to 158°C. m .
[0059] Generally, the crystallization temperature (T c ) is 105 to 120°C, preferably in the range of 100 to 119°C, more preferably in the range of 110 to 118°C. The crystallization temperature (T c ) is measured by DSC according to ISO11357 / 3.
[0060] Generally, the heat of fusion (H m ) is 90 to 110 J / g, preferably in the range of 92 to 108 J / g, more preferably in the range of 95 to 105 J / g. Heat of fusion (H m ) is measured by DSC according to ISO 11357 / 3.
[0061] The weight average molecular weight (Mw) of the high isotactic polypropylene is generally in the range of 80 to 400 kg / mol, preferably in the range of 150 to 380 kg / mol, such as in the range of 200 to 350 kg / mol.
[0062] In another preferred embodiment, the high isotacticity polypropylene has a molecular weight distribution (Mw / Mn) determined by GPC according to ISO 16014 in the range of 2.5 to 4.5, more preferably in the range of 2.7 to 4.2 and even more preferably in the range of 2.8 to 4.0.
[0063] The high isotacticity polypropylene may comprise suitable additives known in the art.According to the present invention, the additives to the high isotacticity polypropylene may be any of those described below in the context of the composition as a whole.
[0064] The high isotactic polypropylene is present in an amount of 80 to 96 wt-% based on the total weight of the polypropylene composition. Preferably, the high isotactic polypropylene is present in an amount of 82 to 95 wt-% relative to the total weight of the polypropylene composition.
[0065] Low isotacticity polypropylene
[0066] Low isotactic polypropylene is a polypropylene homopolymer. According to the present invention, the expression "polypropylene homopolymer" relates to a polypropylene consisting essentially of propylene units, i.e. a polypropylene consisting of at least 99.5 mol %, more preferably at least 99.6 mol %, still more preferably at least 99.7 mol %, such as at least 99.9 mol % of propylene units. In another embodiment, only propylene units are detectable, i.e. only propylene has been polymerized. The definition "propylene homopolymer" has a well-known meaning in the art.
[0067] The low isotacticity homopolymer is a single site catalyst (SSC) based polypropylene, which means that it is prepared in the presence of a single site catalyst. The term "single site catalyst" is well known in the art. In addition, those skilled in the art will understand that polymers prepared using a single site catalyst will have different properties than polymers prepared using alternative catalysts (such as Ziegler-Natta or chromium catalysts).
[0068] Therefore, the low isotacticity polypropylene is obtained by polymerization using a single-site catalyst (preferably a metallocene catalyst). The polymerization method used can be any suitable known polymerization method in the art.
[0069] Compared to polypropylene prepared by using Ziegler-Natta (ZN) catalysts, polypropylene prepared by using metallocenes provides a different microstructure. The most significant difference is the presence of regional defects in metallocene-made polypropylene. These regional defects can be of three different types, namely 2,1-erythro (2,1e), 2,1-threo (2,1t) and 3,1 defects. A detailed description of the structure and formation mechanism of regional defects in polypropylene can be found in Chemical Reviews 2000, 100 (4), pages 1316 to 1327.
[0070] Thus, the term "regio defect" is defined herein as the sum of 2,1 erythro regio defects, 2,1 threo regio defects, and 3,1 regio defects. Thus, the amount of defects (i.e., regio defects, such as 2,1 regio defects (i.e., 2,1 erythro regio defects and 2,1 threo regio defects) and 3,1 regio defects) is expressed as "mol %" of the average percentage of propylene units in the polymer chain.
[0071] In a preferred embodiment, the low isotactic polypropylene homopolymer has a molecular weight in the range of 0.01 to 1.0 mol%, preferably in the range of 0.02 to 0.8 mol%, even more preferably in the range of 0.03 to 0.5 mol% and most preferably in the range of 0.05 to 0.2 mol%. 13 [2,1]-regio defects determined by C-NMR spectroscopy. The presence of such amounts of regio defects is a sufficient (although not mandatory) feature to unambiguously identify that the polypropylene was produced with a metallocene catalyst rather than a Ziegler-Natta type catalyst.
[0072] The metallocene catalyst complex used for preparing low isotacticity polypropylene homopolymer comprises a metallocene complex and a cocatalyst. The metallocene compound or complex is also referred to herein as an organometallic compound (C).
[0073] The organometallic compound (C) comprises a transition metal (M) from Groups 3 to 10 of the Periodic Table of Elements (IUPAC 2007) or an actinide or lanthanide.
[0074] According to the present invention, the term "organometallic compound (C)" includes any metallocene or non-metallocene compound of a transition metal, which carries at least one organic (coordinating) ligand and exhibits catalytic activity alone or together with a cocatalyst. Transition metal compounds are well known in the art, and the present invention encompasses compounds of metals of Groups 3 to 10 of the Periodic Table (IUPAC 2007), for example Groups 3 to 7 or Groups 3 to 6, such as Groups 4 to 6, as well as compounds of lanthanides or actinides.
[0075] In the metallocene catalyst complex used to prepare low isotacticity polypropylene homopolymer, the following preferences apply:
[0076] The complex may have the structure of formula (II):
[0077]
[0078] Wherein each X is independently a halogen atom, C 1-6 -alkyl group, C 1-6 - an alkoxy group, a phenyl group or a benzyl group;
[0079] Each Het is independently a monocyclic or polycyclic heteroaromatic or heterocyclic group containing at least one heteroatom selected from O or S;
[0080] L is -R'2Si-, wherein each R' is independently C 1-20 - a hydrocarbon group or a C substituted group having 1 to 10 carbon atoms 1-10 -alkyl;
[0081] M is Ti, Zr or Hf;
[0082] Each R 1 Same or different and C 1-6 -alkyl group or C 1-6 - alkoxy groups;
[0083] Each n is 1 to 2;
[0084] Each R 2 Same or different and C 1-6 -alkyl group, C 1-6 -alkoxy group or -Si(R)3 group;
[0085] Each R is optionally replaced by 1 to 3 C 1-6 -alkyl substituted C 1-10 - an alkyl or phenyl group; and
[0086] Each p is from 0 to 1.
[0087] Preferably, the compound of formula (II) has structure (II'):
[0088]
[0089] Wherein each X is independently a halogen atom, C 1-6 -alkyl group, C 1-6 - an alkoxy group, a phenyl group or a benzyl group;
[0090] L is Me2Si-;
[0091] Each R 1 Same or different and C 1-6 - alkyl groups, for example methyl or tert-butyl (t-Bu);
[0092] Each n is 1 to 2;
[0093] R 2 is a -Si(R)3 alkyl group; each p is 1;
[0094] Each R is C 1-6 - an alkyl or phenyl group.
[0095] A highly preferred complex of formula (II) is
[0096]
[0097] Most preferably, the complex dimethylsilylenebis[2-(5-trimethylsilylfuran-2-yl)-4,5-dimethylcyclopentadien-1-yl]zirconium dichloride is used.
[0098] To form the catalyst, a cocatalyst (also called activator) is used, which is well known in the art. Cocatalysts containing Al or B are well known and can be used here. It is preferred to use aluminoxanes (e.g. MAO) or boron-based cocatalysts (such as borates).
[0099] The low isotacticity polypropylene homopolymer is characterized by low isotacticity, as that term is defined above. Preferably, the low isotacticity polypropylene homopolymer has 75 to 90 mol%, preferably 80 to 89 mol%, most preferably 82 to 88 mol% of 13 Pentad regularity determined by C-NMR spectroscopy <mmmm>.
[0100] The melt flow rate MFR2 (230°C, 2.16 kg) of the low isotactic polypropylene homopolymer, determined according to ISO 1133, is typically in the range of 1 to 100 g / 10 min, preferably in the range of 10 to 80 g / 10 min, still more preferably in the range of 20 to 60 g / 10 min.
[0101] The low isotactic polypropylene homopolymer is characterized by a moderate amount of cold xylene soluble (XCS) content, and in fact it is required that the component has a xylene cold soluble (XCS) content according to ISO 16152 in the range of 2 to 10 wt.-% relative to the total weight of the low isotactic polypropylene homopolymer. Thus, the low isotactic polypropylene homopolymer preferably has a xylene cold soluble (XCS) content in the range of 2.5 to 9.0 wt.-%, more preferably in the range of 3.0 to 8.5 wt.-%, still more preferably in the range of 4.0 to 8.0 wt.-%.
[0102] The amount of xylene cold solubles (XCS) also indicates that the low isotactic polypropylene homopolymer preferably does not contain any elastomeric polymer components, such as ethylene propylene rubber. In other words, the low isotactic polypropylene homopolymer is preferably not a heterophasic polypropylene, i.e. a system consisting of a polypropylene matrix in which an elastomeric phase is dispersed. Such a system is characterized by a relatively high xylene cold soluble content. In other words, the low isotactic polypropylene is a single-phase polypropylene. Further, the low isotactic polypropylene is preferably a crystalline propylene polymer. The term "crystalline" means that the low isotactic polypropylene has a relatively high melting temperature. In particular, the low isotactic polypropylene has a melting temperature (T) measured by differential scanning calorimetry (DSC) according to ISO 11357 in the range of 135 to 147°C, preferably in the range of 136 to 145°C, and more preferably in the range of 138 to 142°C. m ).
[0103] Typically, the crystallization temperature (T c ) is in the range of 90 to 110°C, preferably in the range of 92 to 108°C, more preferably in the range of 95 to 105°C. The crystallization temperature (T c ) is measured by DSC according to ISO11357 / 3.
[0104] Typically, the heat of fusion (H m ) is 70 to 90 J / g, preferably in the range of 72 to 88 J / g, more preferably in the range of 75 to 85 J / g. Heat of fusion (H m ) is measured by DSC according to ISO 11357 / 3.
[0105] The weight average molecular weight (Mw) of the low isotactic polypropylene homopolymer is typically in the range of 80 to 300 kg / mol, preferably in the range of 100 to 250 kg / mol, such as in the range of 120 to 200 kg / mol.
[0106] In another preferred embodiment, the low isotacticity polypropylene homopolymer has a molecular weight distribution (Mw / Mn) determined by GPC according to ISO 16014 in the range of 2.5 to 4.5, more preferably in the range of 2.6 to 4.0, even more preferably in the range of 2.7 to 3.5.
[0107] The low isotacticity polypropylene homopolymer may comprise suitable additives known in the art.According to the present invention, the additives to the low isotacticity polypropylene may be any of those described below in the context of the composition as a whole.
[0108] The low isotacticity polypropylene homopolymer is present in an amount of 4 to 20 wt% based on the total weight of the polypropylene composition. Preferably, the low isotacticity polypropylene is present in an amount of 5 to 15 wt% relative to the total weight of the polypropylene composition.
[0109] Polypropylene composition
[0110] The polypropylene composition is characterized by having a melt flow rate (MFR2) of 1 to 100 g / 10 min when measured at 230°C under a load of 2.16 kg according to ISO 1133. Preferably, the polypropylene composition has an MFR2 in the range of 1.5 to 50 g / 10 min, more preferably in the range of 2.0 to 40 g / 10 min, such as in the range of 2.5 to 30 g / 10 min.
[0111] Typically, the polypropylene composition of the present invention has a haze value of 30 to 70%, preferably 40 to 65%, more preferably 50 to 60%. The haze value is measured according to ASTM D1003 on injection molded plaques with a thickness of 1 mm produced as described in EN ISO 1873-2.
[0112] Typically, the melting temperature (T m ) is 145 to 160°C, such as 148 to 158°C, preferably in the range of 150 to 156°C. The melting temperature (T m ) is measured by DSC according to ISO 11357 / 3.
[0113] Typically, the crystallization temperature (T c ) is in the range of 90 to 120°C, preferably in the range of 100 to 119°C, more preferably in the range of 110 to 118°C. The crystallization temperature (T c ) is measured by DSC according to ISO 11357 / 3.
[0114] Typically, the heat of fusion (H m ) is 80 to 105 J / g, preferably in the range of 85 to 103 J / g, more preferably in the range of 90 to 100 J / g. Heat of fusion (H m ) is measured by DSC according to ISO 11357 / 3.
[0115] Typically, the polypropylene composition of the present invention has a relative strain at break determined in a tensile test on injection molded specimens according to ISO 527-2 of at least 70% when measured after 7 days. More preferably, the relative strain at break under these conditions is in the range of 70% to 99%, such as 80% to 99%.
[0116] Furthermore, the polypropylene composition of the present invention has, after exposure to γ-radiation at an intensity of 50 kGy, an ideal relative strain at break determined in a tensile test on injection molded specimens according to ISO 527-2 of at least 10% when measured after 7 days. More preferably, the relative strain at break under these conditions is in the range of 10% to 60%, such as 11% to 50%.
[0117] Although it is within the scope of the present invention that the polypropylene composition further comprises other polymers in addition to the high isotacticity polypropylene and the low isotacticity polypropylene, it is preferred that the high isotacticity polypropylene and the low isotacticity polypropylene are the only polymer components in the polypropylene composition. It should be understood that the polymer composition may further contain standard polymer additives (which may be part of a masterbatch).
[0118] Examples of additives include, but are not limited to, stabilizers such as antioxidants (e.g., hindered phenols, phosphites / phosphonates, alkyl radical scavengers, aromatic amines, or blends thereof), metal deactivators (e.g., MD 1024) or UV stabilizers. Other typical additives are modifiers such as antistatic agents or antifogging agents (e.g. ethoxylated amines and amides or glycerides), acid scavengers (e.g. calcium stearate), foaming agents, adhesives (e.g. polyisobutylene), lubricants and resins (e.g. ionomer waxes, polyethylene and ethylene copolymer waxes, Fischer-Tropsch waxes, montan wax-based waxes, fluorine-based compounds or paraffin waxes), and slip agents and anti-caking agents (e.g. erucamide, oleamide, talc, natural and synthetic silica or zeolites) and mixtures thereof.
[0119] Typically, the total amount of additives is in the range of 0.1 to 5.0 wt%, preferably in the range of 0.1 to 2.0 wt%, more preferably in the range of 0.1 to 1.5 wt%.The amount of additives is relative to the total amount of the polypropylene composition.
[0120] In a particular embodiment the polypropylene composition comprises a UV stabilizer.
[0121] The polypropylene composition of the present invention is typically prepared by extruding a high isotacticity polypropylene in the presence of a low isotacticity polypropylene and any other optional components.
[0122] At the end of the extruder, a polypropylene composition melt is obtained. The polypropylene composition melt of the present invention can then be passed through a die in an optional die zone of the extruder. When the polypropylene composition melt of the present invention passes through the die, it is usually further cooled and pelletized.
[0123] The die section usually includes a die plate, which is usually a thick metal disk with a plurality of holes. These holes are parallel to the screw axis.
[0124] The pelletizer is usually a strand pelletizer or an underwater pelletizer.
[0125] application
[0126] The present invention also provides an article comprising the polypropylene composition of the present invention. Suitable articles are films, such as, for example, cast films and injection molded articles. A preferred injection molded article is an element of a packaging system, such as a closure cap, a screw cap or a closure system for food or fluid packaging. Another preferred injection molded article is a medical article, such as an element of a diagnostic system or a syringe.
[0127] use
[0128] The present invention further relates to the use of a SSC-catalyzed low isotacticity propylene homopolymer of the propylene composition described hereinbefore for improving the ductility retention measured as relative strain at break after 7 days.
[0129] The invention will now be described with reference to the following non-limiting examples.
[0130] Figure 1 : Ductility retention of the composition of the invention and the comparative composition after γ-irradiation with an intensity of 50 kGy when annealed at 80°C (values for 1 week and 8 weeks)
[0131] Figure 2 : Ductility retention of the composition of the present invention and the comparative composition when annealed at 80°C (values for 1 week and 8 weeks)
[0132] Examples
[0133] Determination method
[0134] Melt flow rate
[0135] The melt flow rate (MFR) is determined according to ISO 1133 and is expressed in g / 10 min. The MFR indicates the fluidity and, therefore, the processability of a polymer. The higher the melt flow rate, the lower the viscosity of the polymer. The MFR2 of polypropylene is determined at a temperature of 230° C. and under a load of 2.16 kg.
[0136] Quantification of microstructure by NMR spectroscopy
[0137] Quantitative nuclear magnetic resonance (NMR) spectroscopy was used to quantify the isotacticity and regioregularity of the polymers.
[0138] Quantitative measurements were recorded in solution using a Broker Advance III 400 NMR spectrometer operating at 400.15 and 100.62 MHz for H and 13C, respectively. 13 C{ 1 H} NMR spectroscopy. Nitrogen was used for all pneumatics and all spectra were 13 C optimized 10mm extended temperature probe was recorded at 125°C. Approximately 200mg of material was dissolved in 3ml of 1,2-tetrachloroethane-d2 (TCE-d2) along with chromium (III) acetylacetonate (Cr(acac)3) to give a 65mM solution of the relaxation agent in the solvent (Singh, G., Kothari, A., Gupta, V., Polymer Testing 28 5 (2009), 475). To ensure a homogeneous solution, the NMR tube was further heated in a rotary oven for at least 1 hour after initial sample preparation in a heating block. After insertion into the magnet, the tube was rotated at 10Hz. This setup was chosen primarily for high resolution and accurate quantification of ethylene content and quantitatively required. Standard single pulse excitation without NOE was used, using an optimized tip angle, a 1 s recycle delay, and a two-stage WALTZ16 decoupling scheme (Zhou, Z., Kuemmerle, R., Qiu, X., Redwine, D., Cong, R., Taha, A., Baugh, D. Winniford, B., J. Mag. Reson. 187 (2007) 225; Busico, V., Carbonniere, P., Cipullo, R., Pellecchia, R., Severn, J., Talarico, G., Macromol. Rapid Commun. 2007, 28, 1128). A total of 6144 (6k) transient values were collected for each spectrum.
[0139] A proprietary computer program was used to quantify 13 C{ 1 H} NMR spectra are processed, integrated and the relevant quantitative properties are determined by integration. Using the chemical shift of the solvent, all chemical shifts are indirectly referenced to the central methylene group of the ethylene block (EEE) at 30.00ppm. Even when the structural unit is not present, this method allows comparable references. Observed the characteristic signal corresponding to the incorporation of ethylene (Cheng, HN, Macromolecules 17 (1984), 1950).
[0140] For polypropylene homopolymer, all chemical shifts were internally referenced to the methyl isotactic pentad (mmmm) at 21.85 ppm.
[0141] Characteristic signals corresponding to regio defects (Resconi, L., Cavallo, L., Fait, A., Piemontesi, F., Chem. Rev. 2000, 100, 1253; Wang, WJ., Zhu, S., Macromolecules 33 (2000), 1157; Cheng, HN, Macromolecules 17 (1984), 1950) or comonomers were observed.
[0142] The tacticity distribution is quantified by integrating the methyl region between 23.6 and 19.7 ppm, correcting for any sites not associated with the stereo sequence of interest (Busico, V., Cipullo, R., Prog. Polym. Sci. 26 (2001) 443; Busico, V., Cipullo, R., Monaco, G., Vacatello, M., Segre, AL, Macromoleucles 30 (1997) 6251). Specifically, the quantitative effects of regio defects and comonomers on the tacticity distribution are corrected by subtracting representative regio defect and comonomer integrals from the specific integrated region of the stereo sequence.
[0143] Isotacticity is determined at the pentad level and reported as the percentage of isotactic pentad (mmmm) sequences relative to all pentad sequences:
[0144] [mmmm]% = 100*(mmmm / sum of all pentads).
[0145] The presence of the 2,1-erythro regio defect is indicated by the presence of two methyl sites at 17.7 and 17.2 ppm and confirmed by the other characteristic sites.
[0146] No characteristic signals corresponding to other types of regional defects were observed (Resconi, L., Cavallo, L., Fait, A., Piemontesi, F., Chem. Rev. 2000, 100, 1253). The average integral of the two characteristic methyl sites at 17.7 and 17.2 ppm was used to quantify the amount of 2,1 erythro regional defects:
[0147] P 21e =(I e6 +I e8 ) / 2
[0148] The amount of 1,2 primary insertion propene was quantified based on the methyl region and corrected for sites not involved in the primary insertion and for primary insertion sites not included in this region:
[0149] P 12 =I CH3 +P 12e
[0150] The total amount of propene is quantified as the sum of the primary inserted propene and all other regio defects present:
[0151] P 总 =P 12 +P 21e
[0152] The mole percentage of 2,1 erythro regio defects relative to all propylene was quantified:
[0153] [21e] mol% = 100*(P 21e / P 总 )
[0154] For copolymers, characteristic signals corresponding to ethylene incorporation were observed (Cheng, HN, Macromolecules 17 (1984), 1950).
[0155] In cases where regio defects are also observed (Resconi, L., Cavallo, L., Fait, A., Piemontesi, F., Chem. Rev. 2000, 100, 1253; Wang, WJ., Zhu, S., Macromolecules 33 (2000), 1157; Cheng, HN, Macromolecules 17 (1984), 1950), it is necessary to correct for the effect of these defects on the comonomer content.
[0156] Number average molecular weight (Mn), weight average molecular weight (Mw) and molecular weight distribution (MWD)
[0157] Molecular weight averages (Mw, Mn) and molecular weight distribution (MWD), ie, Mw / Mn (where Mn is the number average molecular weight and Mw is the weight average molecular weight), were determined by gel permeation chromatography (GPC) according to ISO 16014-4:2003 and ASTM D 6474-99.
[0158] DSC analysis
[0159] Melting temperature (T m ) and crystallization temperature (T c ) and heat of fusion (H m ) were measured on 5 to 10 mg samples using a TA Instrument Q200 differential scanning calorimeter (DSC) according to ISO 11357 / Part 3 / Method C2 under a nitrogen atmosphere of 50 mL / min. Crystallization and melting temperatures were obtained with a heating / cooling / heating cycle between -30 and 225°C at a scanning rate of 10°C / min. The crystallization and melting temperatures were taken from the peaks of the endotherm and exotherm in the cooling step and the second heating step, respectively.
[0160] Xylene soluble content (XCS, weight %)
[0161] The xylene soluble polymer content is determined according to ISO 16152; 5th edition; 2005-07-01 at 25°C.
[0162] Tensile test
[0163] Tensile properties (yield stress, tensile modulus and strain at break) were measured according to ISO 527-2 (crosshead speed = 1 mm / min for the modulus range; test speed 50 mm / min for higher strains; at 23° C.) using injection molded specimens 1A (dog bone shape, 4 mm thickness) prepared as described in EN ISO 1873-2. The first measurement was carried out after a conditioning time of 96 h at 23° C. for the specimens.
[0164] Haze
[0165] Haze is measured according to ASTM D1003 at a thickness of 1 mm and an area of 60 × 60 mm. 2 The results are determined on injection moulded plaques produced as described in EN ISO 1873-2.
[0166] Comonomer content
[0167] Poly(propylene-co-ethylene)-ethylene content by IR spectroscopy
[0168] Quantitative infrared (IR) spectroscopy was used to quantify the ethylene content of poly(ethylene-co-propylene) copolymers by calibration to the primary method.
[0169] By using a set of quantitative 13 In-house non-commercial calibration standards of known ethylene content, determined by C solution state nuclear magnetic resonance (NMR) spectroscopy, facilitate calibration. The calibration procedure was performed in a conventional manner well documented in the literature. The calibration set consisted of 38 calibration standards with ethylene contents ranging from 0.2 to 75.0 wt %, produced at pilot or full scale under a variety of conditions. The calibration set was selected to reflect the typical types of copolymers encountered by the final quantitative IR spectroscopy.
[0170] Quantitative IR spectra were recorded in the solid state using a Bruker Vertex 70 FTIR spectrometer. Spectra were recorded on 300 μm thick 25×25 mm square films prepared by compression molding at 180 to 210° C. and 4 to 6 mPa. For samples with very high ethylene content (>50 mol %), 100 μm thick films were used. A standard transmission FTIR spectrometer was used using a 5000-500 cm -1 spectral range, 6mm aperture, 2cm -1 spectral resolution, 16 background scans, 16 spectral scans, an interferogram zero filling factor of 64 and Blackmann-Harris 3-term apodisation.
[0171] Use the corresponding (CH2) >2 The structural unit is between 730 and 720 cm -1 (A Q ) total area of CH2 rocking deformation (integration method G, limits 762 and 694 cm -1 ) for quantitative analysis. The quantitative band was normalized to the band corresponding to the CH structural unit at 4323 cm -1 (A R ) (integration method G, limit 4650, 4007 cm -1 ). Then the normalized absorbance (A Q / A R ) to predict the ethylene content in weight percent. This calibration curve has been previously constructed by ordinary least squares (OLS) regression of the normalized absorbance measured on the calibration set and the main comonomer content.
[0172] use 13 Poly(propylene-co-ethylene)-ethylene content for calibration by C NMR spectroscopy
[0173] Use for 1 H and 13 Quantitative measurements were recorded in solution on a Bruker Avance III 400 NMR spectrometer operating at 400.15 and 100.62 MHz, respectively. 13 C{ 1 H} NMR spectroscopy. Nitrogen was used for all pneumatics and all spectra were 13 C optimized 10mm extended temperature probe was recorded at 125°C. Approximately 200mg of material was dissolved in 3ml of 1,2-tetrachloroethane-d2 (TCE-d2) along with chromium (III) acetylacetonate (Cr(acac)3) to give a 65mM solution of the relaxation agent in the solvent (Singh, G., Kothari, A., Gupta, V., Polymer Testing 28 5 (2009), 475). To ensure a homogeneous solution, the NMR tube was further heated in a rotary oven for at least 1 hour after initial sample preparation in a heating block. After insertion into the magnet, the tube was rotated at 10Hz. This setup was chosen primarily for high resolution and accurate quantification of ethylene content and quantitatively required. Standard single pulse excitation without NOE was used, with optimized top cone angle, 1s recycle delay and double-stage WALTZ16 decoupling scheme (Zhou, Z., Kuemmerle, R., Qiu, X., Redwine, D., Cong, R., Taha, A., Baugh, D. Winniford, B., J. Mag. Reson. 187 (2007) 225, Busico, V., Carbonniere, P., Cipullo, R., Pellecchia, R., Severn, J., Talarico, G., Macromol. Rapid Commun. 2007, 28, 1128). A total of 6144 (6k) transient values were collected for each spectrum. For quantitative 13 C{ 1 H} NMR spectra are processed, integrated and the relevant quantitative properties are determined from the integrals. All chemical shifts are indirectly referenced to the central methylene group of the ethylene block (EEE) at 30.00 ppm using the chemical shift of the solvent. This method allows comparable references even when this structural unit is not present. Characteristic signals corresponding to the incorporation of ethylene were observed (Cheng, HN, Macromolecules 17 (1984), 1950), and the comonomer fraction was calculated as the fraction of ethylene in the polymer relative to all monomers in the polymer: fE = (E / (P+E). Using the method of Wang et al. (Wang, WJ., Zhu, S., Macromolecules 33 (2000), 1157), by 13 C{ 1 The integration of multiple signals over the entire spectral area in the {H} spectrum quantifies the comonomer fraction. This method was chosen because of its robustness and ability to account for the presence of area defects when necessary. The integration area was slightly adjusted to improve applicability over the entire range of comonomer contents encountered. For systems with very low ethylene content where only isolated ethylene in the PPEPP sequence was observed, the method of Wang et al. was modified to reduce the impact of the integration of sites that no longer exist. This method reduces the overestimation of ethylene content in such systems and is achieved by reducing the number of sites used to determine the absolute ethylene content to the following equation: E=0.5(Sββ+Sβγ+Sβδ+0.5(Sαβ+Sαγ)). By using this set of sites, the corresponding integration equation becomes: E=0.5(I H +I G +0.5(I C +I D )), using the same symbols used in the article by Wang et al. (Wang, WJ., Zhu, S., Macromolecules 33 (2000), 1157). The equation for absolute propylene content was not modified. The mole percent of comonomer incorporation was calculated from the mole fraction: E [mol %] = 100 * fE. The weight percent of comonomer incorporation was calculated from the mole fraction: E [wt %] = 100 * (fE * 28.06) / ((fE * 28.06) + ((1-fE) * 42.08)).
[0174] Gamma sterilization
[0175] Injection molded test specimens 1A (dog bone shape, 4 mm thickness) prepared as described in EN ISO 1873-2 were exposed to γ-ray radiation at 50 kGy using a 60Co γ-ray source. As described below, the samples were aged continuously at 80°C in a circulating air oven for up to 60 days, while non-irradiated samples were also aged in parallel. Once the desired time was reached, the samples were removed from the oven and aged at 23°C for 24 hours before tensile testing according to ISO 527-2.
[0176] Examples of the present invention and comparative examples
[0177] The following materials were used:
[0178] High isotacticity polypropylene homopolymer (SSC_PP) based on single active site catalyst: SSC-PPH based on CAT-A (MFR2 is 3.5g / 10min, T m 155℃, T c 116℃ and H m The polymer had a pentad isotacticity of 97.5 mol % and a [2,1] regio defect content of 0.6 mol %, an XCS content of 0.4 wt %, a weight average molecular weight (Mw) of 324 kg / mol and a molecular weight distribution (MWD) of 3.2. The polymerization and catalyst details are provided below.
[0179] High isotactic polypropylene homopolymer (ZN_PP) based on Ziegler-Natta catalyst: ZNC-PPHHC001A-B1 (MFR2 is 3.3 g / 10 min, T m is 163℃ and T c 116° C.) is a polypropylene homopolymer commercially available from Borealis A / S. The polymer has a pentad isotacticity of 93.1 mol % and no detectable regio defects, and has an XCS content of 2.5 wt %.
[0180] Low isotacticity polypropylene (PP) based on single active site catalyst
[0181] SSC-PPH based on CAT-B (pentad isotacticity of 86.3 mol%, [2,1] regio defect of 0.08 mol%, T m 139℃, T c 101℃, H m The polymer has a weight average molecular weight (Mw) of 149 kg / mol and a molecular weight distribution (MWD) of 2.9; it has an XCS content of 8.0 wt%. The polymerization details are provided below.
[0182] All polymer compositions of the examples of the present invention and the comparative examples were stabilized with 2000 ppm of poly(4-hydroxy-2,2,6,6-tetramethyl-1-piperidinylethanol-alt-1,4-butanedioic acid) available as Tinuvin 622m (supplied by BASF AG, Germany; CAS No. 65447-77-0) as a UV stabilizer, 1000 ppm of tris(2,4-di-tert-butylphenyl) phosphite available as Irgafos 168 (supplied by BASF AG, Germany; CAS No. 31570-04-4) as an antioxidant, and 500 ppm of calcium stearate (CAS No. 1592-23-0) as an acid scavenger.
[0183] Catalyst preparation
[0184] CAT-A
[0185] Catalyst complex
[0186] As described in WO 2019 / 179959, the following metallocene complexes have been used:
[0187]
[0188] Preparation of MAO-silica carrier
[0189] A steel reactor equipped with a mechanical stirrer and a filter screen was flushed with nitrogen and the reactor temperature was set to 20°C. Next, silica (5.0 kg) of the grade DM-L-303 of AGC Si-Tech, pre-calcined at 600°C, was added from the feed bucket, followed by careful nitrogen pressurization and decompression using a manual valve. Then, toluene (22 kg) was added. The mixture was stirred for 15 min. Next, a 30 wt % solution (9.0 kg) of MAO from Lanxess in toluene was added through the feed line at the top of the reactor within 70 min. Then, the reaction mixture was heated to 90°C and stirred for another two hours at 90°C. The slurry was allowed to settle and the mother liquor was filtered off. At 90°C, the catalyst was washed twice with toluene (22 kg), followed by settling and filtering. The reactor was cooled to 60°C and the solid was washed with heptane (22.2 kg). Finally, the MAO treated SiO2 was dried at 60°C under a nitrogen stream for 2 hours and then dried under vacuum (-0.5 barg) with stirring for 5 hours. The MAO treated support was collected as a free flowing white powder which was found to contain 12.2% Al by weight.
[0190] Catalyst system preparation
[0191] At 20°C, 30 wt% MAO (0.7 kg) in toluene was added to a nitrogen blanketed steel reactor by burette. Then, toluene (5.4 kg) was added under stirring. The metallocene complex (93 g) as described above was added from a metal cartridge, followed by rinsing with 1 kg toluene. The mixture was stirred for 60 minutes at 20°C. Then, triphenylcarbonium tetrakis(pentafluorophenyl)borate (91 g) was added from a metal cartridge, followed by rinsing with 1 kg toluene. The mixture was stirred at room temperature for 1 h. The resulting solution was added to the stirred cake of the MAO-silica support prepared as described above within 1 hour. The cake was left for 12 hours, followed by drying for 2 hours at 60°C under a stream of N2, and further dried for 5 hours under vacuum (-0.5 bar gauge) under stirring.
[0192] The dried catalyst was sampled as a pink free-flowing powder containing 13.9% Al and 0.11% Zr.
[0193] CAT-B
[0194] SiO2 loading:
[0195] 10 kg of silica (PQ Corporation ES757, calcined at 600°C) was added from a feed drum and inerted in the reactor until an O2 level below 2 ppm was reached.
[0196] Preparation of MAO / toluene / MC:
[0197] 30 wt % MAO (14.1 kg) in toluene was added from a balance to another reactor, followed by toluene (4.0 kg) at 25°C (oil circulation temperature) and 95 rpm stirring. After the addition of toluene, the stirring speed was increased from 95 rpm to 200 rpm, and the stirring time was 30 min. 477 g of metallocene racemic-dimethylsilylene bis{2-(5-(trimethylsilyl)furan-2-yl}-4,5-dimethylcyclopentadiene-1-yl}zirconium dichloride was added from a metal barrel, followed by 4 kg of toluene rinse (total toluene was 8.0 kg). For MC feed, the reactor stirring speed was changed to 95 rpm, and for 3 h reaction time, the reactor stirring speed was returned to 200 rpm. After the reaction time, the MAO / toluene / MC solution was transferred to the feed container.
[0198] Preparation of catalyst:
[0199] The reactor temperature was set to 10°C (oil circulation temperature), and during the addition of MAO / toluene / MC, the stirring was adjusted to 40 rpm. The MAO / toluene / MC solution (22.2 kg) was added over 205 min, followed by a 60 min stirring time (the oil circulation temperature was set to 25°C). After stirring, the "dry mix" was stabilized at 25°C (oil circulation temperature) for 12 h with stirring at 0 rpm. The reactor was rotated 20° (back and forth), and stirring was turned on several times per hour at 5 rpm.
[0200] After stabilization, the catalyst was dried at 60°C (oil circulation temperature) for 2 h at a nitrogen flow of 2 kg / h, followed by drying under vacuum for 13 h (same nitrogen flow, stirring at 5 rpm). The dried catalyst was sampled and the HC content was measured using thermogravimetry in a glove box with a Sartorius Moisture Analyser (Model MA45). The target HC level was <2% (actual 1.3%).
[0201] polymerization
[0202] Aggregate in a volume of 21.2dm 3 The reaction mixture was stirred in a stirred autoclave. The vacuum autoclave was filled with 5400 g of propylene. 0.25 to 0.50 mmol of triethylaluminum (0.6 mol / l solution in heptane) was added using a 250 g propylene stream. The solution was stirred for at least 20 min at 25 ° C. Then, 6.7 mmol of hydrogen was fed using a flow controller. 1050 to 1150 mg of catalyst was weighed into a steel vial in a glove box and suspended in 3 ml of n-heptane. The vial was attached to the polymerization autoclave and the catalyst was rinsed into the reactor together with an additional 350 g of propylene.
[0203] For the prepolymerization, the reactor was stirred at 25°C for 10 min. Then, the reactor temperature was raised to a bulk temperature of 80°C. When the temperature exceeded 78°C, an additional 15.6 mmol of hydrogen was added using a flow meter and the timing of the bulk polymerization was started. After 240 min of polymerization time, the reactor was flashed to ambient pressure, purged twice with nitrogen and evacuated to remove residual hydrocarbons.
[0204] result
[0205] Two inventive examples and four comparative examples were prepared. Table 1 shows the compositions of the test examples.
[0206] Table 1
[0207] Example ZN_PP SSC_PP PP Acid scavengers Antioxidants UV Stabilizers weight% weight% weight% weight% weight% weight% CE1 99.65 0 0 0.05 0.1 0.2 CE2 94.65 0 5 0.05 0.1 0.2 CE3 84.65 0 15 0.05 0.1 0.2 CE4 0 99.65 0 0.05 0.1 0.2 IE1 0 94.65 5 0.05 0.1 0.2 IE2 0 84.65 15 0.05 0.1 0.2
[0208] All compositions were injection molded into tensile test specimens and subjected to two aging tests up to 8 weeks (1344 h) using test times chosen approximately logarithmically as before:
[0209] - Annealed at 80°C without prior irradiation
[0210] - After 50 kGy gamma irradiation, annealing at 80 °C
[0211] Gamma-irradiation is carried out by conventional methods.
[0212] Table 2 summarizes the basic properties and the relative changes in tensile modulus (TM), yield stress (YS), and break strain (SB).
[0213] In this case, the impact retention is judged by the ductility, i.e. by the relative strain at break (SB rel.). Figure 1 and 2 As shown, improvements are observed with respect to the ZNC-PPH based composition both in the case of irradiation and without irradiation. Although the improvement after γ-irradiation is not as good as expected, it is still better than the ZNC-PPH based composition. In pure annealing, the ductility retention is significantly improved.
[0214] Table 2
[0215] < / mmmm> < / mmmm> < / mmmm> < / mmmm> < / mmmm> < / mmmm>
Claims
1. A polypropylene composition having a melt flow rate (MFR2) of 1 to 100 g / 10 min when measured according to ISO 1133 at 230° C. under a load of 2.16 kg, the composition comprising: a) 80 to 96 wt.-%, based on the total weight of the polypropylene composition, of a high isotacticity polypropylene based on a single site catalyst (SSC), the high isotacticity polypropylene having an MFR2 according to ISO 1133 at 230° C. under a load of 2.16 kg of 1 to 100 g / 10 min and a melting temperature (T) determined by differential scanning calorimetry (DSC) in the range of 148 to 160° C. m ), wherein the high isotacticity polypropylene is (i) a polypropylene homopolymer; or (ii) propylene and selected from ethylene and C4-C 10 A random propylene copolymer of at least one comonomer of an alpha-olefin, wherein the at least one comonomer is present in an amount of up to 0.5 wt. % relative to the total weight of the copolymer; and b) 4 to 20 wt.-%, relative to the total weight of the polypropylene composition, of a low isotacticity polypropylene homopolymer based on a single site catalyst (SSC), the low isotacticity polypropylene homopolymer having a melting temperature (T) determined by differential scanning calorimetry (DSC) in the range of 135 to 147°C. m ) and a xylene cold soluble (XCS) content according to ISO 16152 in the range of 2 to 10 wt.-% relative to the total weight of the low isotacticity propylene homopolymer.
2. The polypropylene composition according to claim 1, wherein a) the high isotacticity polypropylene has 95 to 99.9 mol% of 13 Pentad regularity [mmmm] determined by C-NMR spectroscopy; and / or b) the low isotacticity polypropylene homopolymer has 75 to 90 mol% of 13 Pentad regularity [mmmm] determined by C-NMR spectroscopy.
3. The polypropylene composition according to any one of claims 1 or 2, wherein the single-site catalyst is a metallocene catalyst.
4. The polypropylene composition according to anyone of claims 1 to 3, wherein the high isotacticity polypropylene has an XCS content according to ISO 16152 in the range of less than 2.0 wt.-%.
5. The polypropylene composition according to any one of claims 1 to 4, wherein a) the high isotacticity polypropylene has a molecular weight in the range of 0.3 to 1.5 mol% 13 [2,1]-regio defects as determined by C-NMR spectroscopy; and / or b) the low isotacticity polypropylene homopolymer has a molecular weight in the range of 0.01 to 1.00 mol% by 13 [2,1]-regio defects determined by C-NMR spectroscopy.
6. The polypropylene composition according to any one of claims 1 to 5, wherein a) the high isotacticity polypropylene is present in an amount of 82 to 95 wt.-% relative to the total weight of the polypropylene composition; and / or b) The low isotacticity polypropylene homopolymer is present in an amount of 5 to 15 wt-%, relative to the total weight of the polypropylene composition.
7. The polypropylene composition according to any one of claims 1 to 6, wherein the composition has a melt flow rate (MFR2) according to ISO 1133 at 230°C under a load of 2.16 kg of 1.5 to 50 g / 10 min, preferably 2.0 to 40 g / 10 min, more preferably 2.5 to 30 g / 10 min.
8. The polypropylene composition according to any one of claims 1 to 7, wherein a) the high isotacticity polypropylene has a melt flow rate (MFR2) at 230°C under a load of 2.16 kg according to ISO 1133 of 1.5 to 20 g / 10 min, more preferably 2.0 to 15 g / 10 min; and / or b) the low isotacticity polypropylene homopolymer has a melt flow rate (MFR2) according to ISO 1133 at 230°C under a load of 2.16 kg of 1 to 100 g / 10 min, more preferably 10 to 80 g / 10 min and most preferably 20 to 60 g / 10 min.
9. The polypropylene composition according to any one of claims 1 to 8, wherein the composition has a melting temperature (T ) determined by differential scanning calorimetry (DSC) of 145 to 160°C. m ).
10. The polypropylene composition according to any one of claims 1 to 9, wherein a) the high isotacticity polypropylene has a melting temperature (T) measured by differential scanning calorimetry (DSC) of 150 to 159°C, preferably 152 to 158°C. m ); and / or b) the low isotacticity polypropylene homopolymer has a melting temperature (T) determined by differential scanning calorimetry (DSC) of 136 to 145° C., preferably 138 to 142° C. m ).
11. Polypropylene composition according to anyone of claims 1 to 10, wherein the composition has a relative strain at break determined in a tensile test according to ISO 527-2 on injection moulded specimens of at least 70% when measured after 7 days.
12. The polypropylene composition according to any of claims 1 to 11, wherein the composition after sterilization with gamma-irradiation at an intensity of 50 kGy has a relative strain at break determined in a tensile test according to ISO 527-2 on injection moulded specimens of at least 10% when measured after 7 days.
13. An article comprising the polypropylene composition according to any one of claims 1 to 12, wherein the article is preferably a cast film, an injection moulded article, such as a medical article, a closure cap, a screw cap or a closure system for food or fluid packaging.
14. Use of a single site catalyst low isotacticity polypropylene homopolymer as defined in any one of claims 1 to 12 for improving the ductility retention of a polypropylene composition as defined in any one of claims 1 to 12, said ductility retention being measured as relative strain at break after 7 days according to ISO 527-2.
Citation Information
Patent Citations
Radiation tolerant polypropylene and its useful articles
EP0847420A1
JP1973008419U
Catalysts for olefin polymerization
WO2019179959A1